Ithaca, New York contingent - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows marchers with a banner that reads, "Ithaca, New York, Cornell U., Ithaca Col." during the National March on Washington for Lesbian and Gay Rights.